ANALISIS IMPLEMENTASI KEBIJAKAN PENDIDIKAN KARAKTER DI PERGURUAN TAMAN SISWA KECAMATAN TUREN KABUPATEN MALANG - Acetylena, Sita (Jurnal Kebijakan dan Pengembangan Pendidikan, 2013)
This aims to describe the analysis of policy implementation of character education in SD Taman Siswa, Turen which includes 1) understanding and describing the implementation of Character Education Policy in SD Taman Siswa, Turen, 2) understanding the constraints of the implementation of character education in SD Taman Siswa, Turen 3) finding out the school?s strategies to overcome the obstacles in the implementation of education character in SD Taman Siswa. The study was conducted over three months using a qualitative approach. Data was collected through interviews, observations, and review documents related to this research.. Techniques of data analysis by the presentation of data, data reduction and drawing conclusions. The data analysis begins by describing the findings during the study, then discussed objectively supported by theoretical studies. The conclusion of this study is the policy implementation of education character in SD Taman SiswaTuren run well although there are some constraints. The obstacles are including a lack of professionalism and spirit "Among" of the teachers, the negative effects of globalization to the students, and lack of role of parents and society in the policy implementation of character education. And to overcome these obstacles, do the strategies implemented by 1) increasing the professionalism and spirit "Among" the teacher, 2) implementing the methods of character education with the "ngerti, ngrasa, nglakoni", 3) strengthening the role of parents and communities by increasing the role of school committee.